2019
DOI: 10.1136/bmj.l440
|View full text |Cite
|
Sign up to set email alerts
|

Duration of antibiotic treatment for common infections in English primary care: cross sectional analysis and comparison with guidelines

Abstract: ObjectiveTo evaluate the duration of prescriptions for antibiotic treatment for common infections in English primary care and to compare this with guideline recommendations.DesignCross sectional study.SettingGeneral practices contributing to The Health Improvement Network database, 2013-15.Participants931 015 consultations that resulted in an antibiotic prescription for one of several indications: acute sinusitis, acute sore throat, acute cough and bronchitis, pneumonia, acute exacerbation of chronic obstructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
79
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 40 publications
(62 reference statements)
3
79
0
1
Order By: Relevance
“…Emerging research has also demonstrated that longer antibiotic courses can lead to higher risks of resistance. Thus, providing clear guidance on appropriate antibiotic use in terms of the indications, choice and duration is considered important to help reduce antibiotic resistance 18…”
Section: Introductionmentioning
confidence: 99%
“…Emerging research has also demonstrated that longer antibiotic courses can lead to higher risks of resistance. Thus, providing clear guidance on appropriate antibiotic use in terms of the indications, choice and duration is considered important to help reduce antibiotic resistance 18…”
Section: Introductionmentioning
confidence: 99%
“…The second of the studies, by Pouwels and colleagues (doi:10.1136/bmj.l440), builds on good evidence that “short” antibiotic courses are as effective as “long” courses for most infections treated in primary care 1112. The authors used data from 2013 to 2015 to show convincingly that adhering to the latest national guidance on length of treatment for common infections would result in 14 fewer days of antibiotic use for every 10 prescriptions issued, or to around 65 million fewer antibiotic days each year for the UK 12. This is double the number of antibiotic days that would be saved if the UK were to hit its 2016 target of halving unnecessary antibiotic prescriptions by 2020 (assuming a seven day current average course length) 13…”
mentioning
confidence: 99%
“…Recent clinical trials, for example, have suggested that traditional courses of antibiotics could be shortened without compromising patient safety 37 , 38 , but this latest evidence has not yet been translated into guidelines. Hence, even though IDSA and SPILF guidelines are used widely internationally, their recommendations are by no means undisputed 39 , 40 . This also leaves prescribers more vulnerable to behavioural biases.…”
Section: Discussionmentioning
confidence: 99%